Experimental models to study the immunobiology of hepatitis C virus - Jo, Juandy; Lohmann, Volker; Bartenschlager, Ralf; Thimme, Robert (Journal of general virology, 2011)
Effective host immune responses are essential for the control of hepatitis C virus (HCV) infection and persistence of HCV has indeed been attributed to their failure. In recent years, several in vitro and in vivo experimental models have allowed studies of host immune responses against HCV. Numerous observations derived from these models have improved our understanding of the mechanisms responsible for the host's ability to clear the virus as well as of the mechanisms responsible for the host's failure to control HCV replication. Importantly, several findings obtained with these model systems have been confirmed in studies of acutely or chronically HCV-infected individuals. Collectively, several mechanisms are used by HCV to escape host immune responses, such as poor induction of the innate immune response and escaping/impairing adaptive immunity. In this review, we summarize current findings from experimental models available for studies of the immune response targeting HCV and discuss the relevance of these findings for the in vivo situation in HCV-infected humans.,
Gesehen am 05.07.2022